2009
DOI: 10.1093/jxb/erp165
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial endophyte Trichoderma hamatum isolate DIS 219b promotes growth and delays the onset of the drought response in Theobroma cacao

Abstract: Theobroma cacao (cacao) is cultivated in tropical climates and is exposed to drought stress. The impact of the endophytic fungus Trichoderma hamatum isolate DIS 219b on cacao's response to drought was studied. Colonization by DIS 219b delayed drought-induced changes in stomatal conductance, net photosynthesis, and green fluorescence emissions. The altered expression of 19 expressed sequence tags (ESTs) (seven in leaves and 17 in roots with some overlap) by drought was detected using quantitative real-time reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
195
0
15

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(231 citation statements)
references
References 70 publications
(99 reference statements)
12
195
0
15
Order By: Relevance
“…Several other studies with leaf-cutting ants (Atta and Acromyrmex) suggested that Trichoderma fungi are associated with the plant substrate foraged by workers (Barbosa 2004;Rodrigues et al 2008Rodrigues et al , 2009Rodrigues et al , 2011 Samuels et al 2006;Bae et al 2009;Chaverri et al 2011;Druzhinina et al 2012;Bailey and Melnick 2013). Regarding T. viride, this species was considered to be restricted to the north hemisphere and found in soil, trunks and decaying wood, with only two strains reported in the tropics, isolated as endophytes of Theobroma gileri (Ecuador) and Theobroma cacao (Brazil) (Lieckfeldt et al 1999;Jaklitsch et al 2006;Samuels et al 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several other studies with leaf-cutting ants (Atta and Acromyrmex) suggested that Trichoderma fungi are associated with the plant substrate foraged by workers (Barbosa 2004;Rodrigues et al 2008Rodrigues et al , 2009Rodrigues et al , 2011 Samuels et al 2006;Bae et al 2009;Chaverri et al 2011;Druzhinina et al 2012;Bailey and Melnick 2013). Regarding T. viride, this species was considered to be restricted to the north hemisphere and found in soil, trunks and decaying wood, with only two strains reported in the tropics, isolated as endophytes of Theobroma gileri (Ecuador) and Theobroma cacao (Brazil) (Lieckfeldt et al 1999;Jaklitsch et al 2006;Samuels et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Trichoderma is cosmopolitan , occurring on various substrates in different parts of the world, including: (i) soil; (ii) decaying wood; (iii) on edible mushrooms and (iv) as endophytes in plants Hanada et al 2008;Bae et al 2009;Chaverri et al 2011;Druzhinina et al 2012;Bailey and Melnick 2013;. Due to the diversity of substrates collected by attine ants, their colonies represent potential resources for the discovery of new Trichoderma species.…”
Section: Discussionmentioning
confidence: 99%
“…have beneficial effects on plants. For instance, there are commercial agricultural products containing T. atroviride, T. harzianum and T. hamatum (Ha, 2010) that promote plant growth (Chang et al ., 1986; Gravel et al ., 2007; Contreras‐Cornejo et al ., 2009), reduce the severity of plant diseases (Naseby et al ., 2000; Nawrocka and Malolepsza, 2013) and enhance tolerance to abiotic stresses (Bae et al ., 2009; Montero‐Barrientos et al ., 2010; Dixit et al ., 2011; Contreras‐Cornejo et al ., 2014). In addition, Trichoderma sp.…”
Section: Discussionmentioning
confidence: 99%
“…Several epiphytic and endophytic Trichoderma species and strains are already being well studied and further recommended as potential biological control agents against phytophatogenic fungi such as Phytophthora capsici in hot pepper [52], Moniliophthora roreri, M. fide, M. perniciosa, and Phytophthora species in cacao trees [43,53]. Trichoderma strains being studied for their potential to control cacao diseases and ameliorate damage caused by abiotic stresses also have an ability to alter cacao gene expression during colonization [43].…”
Section: Endophytic Trichoderma Strains Exhibit High Antifungal Potenmentioning
confidence: 99%